2015
DOI: 10.1002/clc.22428
|View full text |Cite
|
Sign up to set email alerts
|

Burden of First and Recurrent Cardiovascular Events Among Patients With Hyperlipidemia

Abstract: Background: Acute cardiovascular (CV) events have been evaluated in patients with specific comorbidities but have not focused on patients with hyperlipidemia or on the their long-term costs. Objectives: To evaluate incidence of CV events, costs, and resource utilization among patients with hyperlipidemia and baseline risk of CV disease (CVD). Methods: Patients (age 18 to 64 years) diagnosed with hyperlipidemia or using lipid-modifying medications were identified from administrative claims. Patients were catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 17 publications
5
33
0
2
Order By: Relevance
“…Two US claims database Table 5. analyses 6,38 reported a 43% subsequent CV event risk over 2-3 years of follow-up for patients with a history of MI, stroke, UA, or revascularization. CV event risk was 49% over 2 years among a Swedish cohort of patients with a history of CVD 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two US claims database Table 5. analyses 6,38 reported a 43% subsequent CV event risk over 2-3 years of follow-up for patients with a history of MI, stroke, UA, or revascularization. CV event risk was 49% over 2 years among a Swedish cohort of patients with a history of CVD 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is the underlying cause of most clinical CV events 3 , including coronary heart disease (CHD), acute coronary syndromes (ACS) such as myocardial infarction (MI) or unstable angina (UA), peripheral artery disease (PAD), heart failure (HF), transient ischemic attack, ischemic stroke (IS), and CV-related death 1,4 . Recent studies have shown that 15%-43% (over 2-3 years) of patients with a primary CV event will experience a second CV event 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…В условиях демографического старения популяции в РФ общее число лиц с этими нарушениями The Economic Burden of Hypercholesterolemia in the RF Экономический ущерб от гиперхолестеринемии в РФ будет возрастать, увеличивая затраты системы здравоохранения и государства в целом. Затраты системы здравоохранения, ассоциированные с сердечно-сосудистыми событиями у лиц с ГХС, продемонстрированы в ряде исследований [11,12,43]. Так, португальские исследователи показали, что в ценах 2013 г. прямые затраты, ассоциированные с ГХС, составили €320 млн, а непрямые, связанные с выплатами по инвалидности -€198 млн [44].…”
Section: результатыunclassified
“…Previous research has been valuable in demonstrating the great cost burden of CVEs [ 8 , 16 , 20 22 ], yet only one report specifically assessed cohorts of patients with hyperlipidemia. Given that adequate hyperlipidemia treatment lowers the risks associated with CVEs, it is important to obtain current cost estimates associated with CVEs.…”
Section: Introductionmentioning
confidence: 99%